Prevalence of work-related musculoskeletal disorders among pediatric long-term ventilatory care unit nurses: Descriptive cross-sectional study - Brightlin Nithis Dhas (13767527) (2022)
Purpose Prevalence of musculoskeletal disorders (MSD) is widely reported among nurses but not specific to nurses working in pediatric long-term ventilatory care (PLTVC) units. The purpose of this study is to determine the prevalence of MSD among nurses working in PLTVC settings. Design and methods Cross-sectional descriptive design. Using the Extended Nordic Musculoskeletal Questionnaire, 127 nurses working in PLTVC units were recruited to examine the prevalence of single-site, two-site, and multi-site MSDs in nine body parts. Results 90.6% of participants reported a lifetime prevalence of MSD in single site, 95% CI [84.21, 94.51]; 53.5% in two-sites, 95% CI [44.89, 61.99]; 46% in multi-sites, CI [28.38, 44.87]. The most common pain site was lower back (55.1%) followed by neck (35.4%), shoulder (33.9%), upper back (29.1%), wrist/hand (17.3%), ankle/ft (15.7%), knee (15%), hips/thighs (11.8%), and elbow (7.9%). There was a statistically significant difference in participants' years of experience in PLTVC among those reporting multi-site pain (M = 6.10, SD = 5.58) and the rest (M = 3.77, SD = 3.84) of the group reporting no pain or pain in one or two sites; t = (2.77), p = .006, 95% CI [0.66, 3.98]. Conclusions There is a high prevalence of MSD among PLTVC nurses. There seems to be a relationship between years of experience in PLTVC settings and multi-site pain. Practice implications PLTVC nurses must take additional precautions, since working in this environment increases the possibility of developing pain in multiple sites, particularly if they have been working for more than six years. Other Information Published in: Journal of Pediatric Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pedn.2022.12.015